2022
DOI: 10.1371/journal.pone.0266542
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptome analyses highlight multiple pathways involved in drought stress in Medicago falcata

Abstract: Medicago falcata is one of the leguminous forage crops, which grows well in arid and semiarid region. To fully investigate the mechanism of drought resistance response in M. falcata, we challenged the M. falcata plants with 30% PEG-6000, and performed physiological and transcriptome analyses. It was found that, the activities of antioxidant enzymes (eg. SOD, POD, and CAT) and soluble sugar content were all increased in the PEG-treated group, as compared to the control group. Transcriptome results showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The abundances of pyruvate, phosphate dikinase, and phosphoenolpyruvate carboxykinase increased, consuming ATP to convert pyruvate into phosphoenolpyruvate and participating in the process of gluconeogenesis. The glycolysis/gluconeogenesis pathway in plants has been repeatedly confirmed to be involved in the drought response [ 21 , 22 ], which may play a major role in accumulating sugars and protecting cells. We determined the soluble sugar content in the leaves of the drought and MC treatment groups, as shown in Figure 7 , and found that the soluble sugar content in the leaves increased by 8.41% after MC pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…The abundances of pyruvate, phosphate dikinase, and phosphoenolpyruvate carboxykinase increased, consuming ATP to convert pyruvate into phosphoenolpyruvate and participating in the process of gluconeogenesis. The glycolysis/gluconeogenesis pathway in plants has been repeatedly confirmed to be involved in the drought response [ 21 , 22 ], which may play a major role in accumulating sugars and protecting cells. We determined the soluble sugar content in the leaves of the drought and MC treatment groups, as shown in Figure 7 , and found that the soluble sugar content in the leaves increased by 8.41% after MC pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoid biosynthesis pathways have been reported to be enhanced in plants under environmental stress, which, in turn, increases carotenoid content [22]. Fatty acids were beneficial to plant resistance to environmental stress, and the higher their content, the stronger plant resistance to environmental stress [23]. The increased capacity of pentose and glucuronate interconversions was beneficial in improving carbohydrate and energy metabolism, which, in turn, promoted plant metabolism and enhanced plant resistance to environmental stress [24].…”
Section: Kegg Pathway Enrichment and Functional Analysis Of Key Genesmentioning
confidence: 99%
“…Plants respond to drought by increasing antioxidant enzyme activity, which removes reactive oxygen species to alleviate stress caused by drought. In the antioxidant enzyme system, superoxide radicals can be made disproportionate to H 2 O 2 and O 2 by SOD (superoxide dismutase), while H 2 O 2 is broken down by POD (peroxidase) and CAT (catalase) [12]. In addition to enzymatic antioxidants (e.g., antioxidant enzymes such as SOD and POD), non-enzymatic antioxidants (e.g., flavonoids) are also involved in antioxidant defense in plants.…”
Section: Introductionmentioning
confidence: 99%